Agile manufacturing framework and practice. (31st January 2006) - Ismail, Hossam S.; Snowden, Simon P.; Poolton, Jenny; Reid, R., Ivan C. Arokiam
This paper presents a framework for the implementation of agile manufacturing. The framework employs a bottom-up approach taking the company through three iterative implementation phases of robustness of operation, responsiveness to customers and proactive growth tactics. The framework incorporates a detailed assessment of the level of business environment turbulence and the impact of this turbulence on the enterprise. The results of this assessment are used to identify and customise an implantation plan as well as select the required tools and those measures of performance necessary to monitor the plans progress. This is carried while aligning any action to the company strategy.